PENINGKATAN HASIL BELAJAR PKN MELALUI MODEL BASED LEARNING BERBANTUAN MEDIA WORDWALL KELAS IV SD INPRES JONGAYA KOTA MAKASSAR - Aulia Eka Putri; Amelia; Anisa (STKIP Subang, 2024)
This study aims to improve the learning outcomes of Civics by implementing a based learning model assisted by wordwall media for fourth grade students of SD Inpres Jongaya. This study uses the PTK (Classroom Action Research) method which consists of 2 cycles. Each cycle has 4 stages, consisting of: planning, implementing actions, observation and reflection. The research instrument uses observation sheets and learning outcome tests. Observation, learning outcome tests and documentation are used as data collection techniques. The data analysis techniques used are quantitative and qualitative analysis. The results of the study showed that in cycle I the average score was 69.4, in cycle II the student learning outcome score was higher, namely the average score reached 87.2. In cycle I only 10 students (37%) achieved completion. In contrast to cycle II, which achieved completion as many as 26 students (96%). This shows that classical learning completion was achieved in cycle II, because the number of students was more than 80%. Thus it can be concluded that the application of the based learning model assisted by wordwall media in Civics subjects can improve student learning outcomes.